Legislative Construction of the Post Amendment In Restoring Indonesian Democracy - Hidayat, Asep Syarifuddin (Jurnal Cita Hukum, 2019)
Abstract.Restoring the face of Indonesian Democracy is complicated. Long phases in any case are needed until the real of Indonesian democracy is obtained. Constitutional amendments were also carried out to restore the meaning of democracy to achieve the benefits of democracy itself. As a result of the constitution being considered sacred and cannot be touched by the idea of change during the New Order, amendments became the only unavoidable alternative. The amendments were undergone in an effort to touch on the elements that are considered as the joint foundation of the establishment of democracy in this country. The things done in the amendments also relate to strengthening the contents of the institution which is the mandate of the constitution. Legislative construction is considered as the base of the joint which is the estuary of the concept of pure democracy. The addition of the DPD organs as a new institution in the Indonesian constitutional legislative structure is part of an effort to restore democracy in Indonesia. Therefore this construction effort has an impact on the opening of access to democracy so that it is no longer distant from the people, guaranteed individual and group freedom, upholding human rights, and opening the space for freedom for the press.Keywords: Construction, Legislative Institution, Indonesian Democracy AbstrakTema yang disandingkan dalam demokrasi yang pernah dilaksananakan di negara Indonesia adalah bentuk upaya para pemimpin untuk menemukan jati diri demokrasi yang sesuai dengan karakter bangsa serta dikehendaki oleh rakyat Indonesia. Berbagai langkah pun ditempuh untuk menemukan makna demokrasi sesungguhnya. Bahkan Amandemen pun dilakukan untuk mengembalikan makna demokrasi guna mencapai manfaat dari demokrasi itu sendiri sebagimana yang dikatakan dalam para ahli hukum. Akibat konstitusi tidak dapat disentuh oleh ide perubahan, maka amandemen pun tidak dapat dihindari. Amandemen dilakukan dalam upaya menyentuh unsur-unsur yang dianggap sebagai pangkal sendi dari tegaknya demokrasi di Negara ini. Tidak hanya mengisi muatan kosong dalam konstitusi, hal lain yang dilakukan amandemen yakni juga terkait penguatan isi lembaga yang merupakan amanat konstitusi. Konstruksi legislatif dianggap sebagai pangkal sendi yang menjadi muara konsep demokrasi murni.  Penambahan organ DPD dalam struktur legislatif ketatanegaraan Indonesia, salah satu usaha merestorasi demokrasi di Indonesia. Membuka akses demokrasi agar tidak berjarak dengan rakyat, menjamin kebebasan individu juga kelompok, menegakkan azasi manusia, memberi ruang untuk pers adalah beberapa materi yang dititipkan dalam mengfungsikan lembaga legislatif sebagai lembaga yang independen representasi rakyat. Lembaga lain dalam struktur legislatif yakni DPD yang lahir bersamaan amandemen ketiga UUD 1945 pada November tahun 2001, juga dibentuk dalam rangka pemenuhan demokrasi rasa keadilan bagi masyarakat di daerah yang tidak terjangkau secara geografis, juga keterbatasan akses terhadap perwakilannya. Kata Kunci: Kontruksi, Lembaga Legislatif, Demokrasi Indonesia Аннотация.В любом случае необходимы длинные фазы, пока не будет достигнута подлинная демократия Индонезии. Были также внесены конституционные поправки, чтобы восстановить значение демократии для достижения преимуществ самой демократии. В результате того, что конституция считается священной и не может быть затронута идеей изменений во время Нового порядка, поправки стали единственной неизбежной альтернативой. Поправки были внесены в попытке затронуть элементы, которые рассматриваются как совместный фундамент установления демократии в этой стране. То, что сделано в поправках, также касается укрепления содержания института, который является мандатом конституции. Законодательное строительство рассматривается как основа объединения, которое является устоявшимся понятием чистой демократии. Добавление органов DPD (региональное представительство) в качестве нового института в конституционную законодательную структуру Индонезии является частью усилий по восстановлению демократии в Индонезии. Поэтому эти усилия по строительству оказывают влияние на открытие доступа к демократии, так что она больше не находится на расстоянии от людей, гарантируется индивидуальная и групповая свобода, отстаиваются права человека и открываются возможности для прессы.Ключевые Слова: строительство, законодательное учреждение, индонезийская демократия